Impacts of aging on murine cartilage biomechanics and chondrocyte in situ calcium signaling. (November 2022) - Fan, Mingyue; Wang, Chao; Kwok, Bryan; Kahle, Elizabeth R.; He, Lan; Lucas Lu, X.; Mauck, Robert L.; Han, Lin
Abstract: Aging is the most prominent risk factor for osteoarthritis onset, but the etiology of aging-associated cartilage degeneration is not fully understood. Recent studies by Guilak and colleagues have highlighted the crucial roles of cell-matrix interactions in cartilage homeostasis and disease. This study thus quantified aging-associated changes in cartilage biomechanics and chondrocyte intracellular calcium signaling, [Ca 2+ ] i, activities in wild-type mice at 3, 12 and 22 months of age. In aged mice, articular cartilage exhibits reduced staining of sulfated glycosaminoglycans (sGAGs), indicating decreased aggrecan content. On cartilage surface, collagen fibrils undergo significant thickening while retaining their transverse isotropic architecture, and exhibit signs of fibril crimping in the 22-month group. These compositional and structural changes contribute to a significant decrease in cartilage modulus at 22 months of age (0.55 ± 0.25 MPa, mean ± 95 % CI, n  = 8) relative to those at 3 and 12 months (1.82 ± 0.48 MPa and 1.45 ± 0.46 MPa, respectively, n  ≥ 8). Despite the decreases in sGAG content and tissue modulus, chondrocytes do not exhibit significantly demoted [Ca 2+ ] i activities in situ, in both physiological (isotonic) and osmotically instigated (hypo- and hypertonic) conditions. At 12 months of age, there exists a sub-population of chondrocytes with hyper-active [Ca 2+ ] i responses under hypotonic stimuli, possibly indicating a phenotypic shift of chondrocytes during aging. Together, these results yield new insights into aging-associated biomechanical and mechanobiological changes of murine cartilage, providing a benchmark for elucidating the molecular mechanisms of age-related changes in cell-matrix interactions.